Teaching urban youth about controversial issues: Pathways to becoming active and informed citizens. (August 2015) - Lin, Alex Romeo; Lawrence, Joshua Fahey; Snow, Catherine Elizabeth
Although American schools are required to meet civic education goals of preparing students to become active and informed citizens, high-quality civic opportunities (e.g. service learning and volunteering) are consistently less available to youth of color who are typically enrolled in schools located in high-poverty communities. The purpose of this study is to evaluate efficacy of the Word Generation program to improve students' self-reported civic engagement ( N = 5798) in the context of a randomized trial that was conducted in several middle schools located in a West Coast metropolitan area of the United States. Word Generation is a cross-content literacy program that instructs students to learn academic words, which are embedded in brief passages covering a different controversial issue each week. Participants completed survey items on how often they helped their friends, community, and school, as well as voting interest. Results provide support for the primary research question – participation in the Word Generation program has a significant impact on students' self-reported civic engagement, but not for voting interest. These results suggest that students' opportunities to debate on social issues are crucial to envisioning oneself as an active participant in civic affairs.